Assessment of Sleep Patterns and Their Correlation with Height in Children Aged 8–11 Years: Insights from the Sleep Disturbance Scale for Children (SDSC) - Ahmad mahfur; Laksmitha Saktiono Safitri; Hawin Nurdiana; Annisa Nurul Arofah (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Sleep plays a crucial role in human growth, particularly during slow-wave sleep when the growth hormone functions optimally. Sleep disturbances are prevalent in 20–30% of children. Over the past century, there has been a notable decline in children’s sleep duration, with the most significant reductions observed in school-aged children. This study investigates the relationship between sleep patterns and the height of boys aged 8–11 years at Muhammadiyah 4 Elementary School in Malang. A cross-sectional design was employed, involving 98 boys who met the inclusion criteria. Data on height and weight were collected from school records, while sleep pattern information was obtained through parent-completed questionnaires. Statistical analysis was conducted using Fisher's exact test with a significance level of p ≤ 0.05. The results revealed no significant association between sleep patterns and children's height (p = 0.649). Most participants were 8 years old, with poor sleep patterns observed. However, based on maternal and paternal height, the majority were categorized as having an appropriate height. This study concludes that there is no significant relationship between sleep patterns and the height of boys aged 8–11 years at Muhammadiyah 4 Elementary School in Malang